Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons. - Screaton, G; Bell, M; Jackson, D; Cornelis, F; Gerth, U; Bell, J (1992)
The CD44 molecule is known to display extensive size heterogeneity, which has been attributed both to alternative splicing and to differential glycosylation within the extracellular domain. Although the presence of several alternative exons has been partly inferred from cDNA sequencing, the precise intron-exon organization of the CD44 gene has not been described to date to our knowledge. In the present study we describe the structure of the human CD44 gene, which contains at least 19 exons spanning some 50 kilobases of DNA. We have identified 10 alternatively spliced exons within the extracellular domain, including 1 exon that has not been previously reported. In addition to the inclusion or exclusion of whole exons, more diversity is generated through the utilization of internal splice donor and acceptor sites within 2 of the individual exons. The variation previously reported for the cytoplasmic domain is shown to result from the alternative splicing of 2 exons. The genomic structure of CD44 reveals a remarkable degree of complexity, and we confirm the role of alternative splicing as the basis of the structural and functional diversity seen in the CD44 molecule.